Eco-friendly, highly stable and efficient nanostructured p-type N-doped ZnO photocatalyst for environmentally benign solar hydrogen production - Bhirud, Ashwini P.; Sathaye, Shivaram D.; Waichal, Rupali P.; Nikam, Latesh K.; Kale, Bharat B. (Green Chemistry, 2012)
We have investigated an economical green route for the synthesis of a p-type N-doped ZnO photocatalyst by a wet chemical method. Significantly, hazardous H2S waste was converted into eco-friendly hydrogen energy using the p-type N-doped ZnO photocatalyst under solar light, which has previously been unattempted. The as-synthesized p-type N-doped ZnO shows a hexagonal wurtzite structure. The optical study shows a drastic shift in the band gap of the doped ZnO in the visible region (3.19-2.3 eV). The doping of nitrogen into the ZnO lattice is conclusively proved from X-ray photoelectron spectroscopy analysis and Raman scattering. The morphological features of the N-doped ZnO are studied from FESEM, TEM and reveal particle sizes to be in the range of similar to 4-5 nm. The N-doped ZnO exhibits enhanced photocatalytic hydrogen generation (similar to 3957 mu mol h(-1)) by photodecomposition of hydrogen sulfide under visible light irradiation, which is much higher as compared to semiconductor metal oxides reported so far. It is noteworthy that a green catalyst is investigated to curtail H2S pollution along with production of hydrogen (green fuel) using solar light, i.e., a renewable energy source. The green process investigated will have the potential to synthesize other N-doped metal oxides.